A Nation of Immigrants: Assimilation and Economic Outcomes in the Age of Mass Migration - Abramitzky, Ran; Boustan, Leah Platt; Eriksson, Katherine (Journal of Political Economy, 2014)
During the Age of Mass Migration (1850-1913), the United States maintained an open border, absorbing 30 million European immigrants. Prior cross-sectional work finds that immigrants initially held lower-paid occupations than natives but converged over time. In newly assembled panel data, we show that, in fact, the average immigrant did not face a substantial occupation-based earnings penalty upon first arrival and experienced occupational advancement at the same rate as natives. Cross-sectional patterns are driven by biases from declining arrival cohort skill level and departures of negatively selected return migrants. We show that assimilation patterns vary substantially across sending countries and persist in the second generation.